Adverse Events of DOACs in Children - Bosch, Alessandra; Albisetti, Manuela (Frontiers in Pediatrics, 2022)
Venous thromboembolism (VTE) has an increasing rate of significance in pediatric patients. The currently standardized anticoagulants (unfractionated heparin, low molecular weight heparin and vitamin K antagonists) and their dose regimens were not comprehensively trialed in pediatric patients. Recently, several direct oral anticoagulants (DOACs) have been studied in clinical trials in the pediatric population and further trials are ongoing. Dabigatran etexilate and rivaroxaban results show that these DOACs are safe and efficient in the treatment and secondary prevention of pediatric VTE. This review will focus on adverse events (AEs) between specific DOACs reported in the clinical trials in children and compare them to standard of care. This will assist clinicians in decision making of selecting the right anticoagulation for their pediatric patients.